The Importance of Biophilic Cities for Local Communities - Marta SZAJA (Communications of International Proceedings, 2020)
The aim of this article is an attempt to show the relations between integrating green and natural elements into building, neighborhood and city design, and providing the basis for healthier lives and lifestyles, e.g. reduction in stress and increased levels of physical and mental health. This paper presents a research study which adopts a qualitative, inductive case study approach. The author used the following two methods to distil and connect research results focused on bringing nature into urban areas and its favorable consequences for local communities: literature review and case studies. The literature review provides an insight into the existing experience in integrating nature into urban areas to provide health and well-being benefits for citizens. The article also considers four case studies of cities around the world. In each city the biophilic elements of the urban structure were used in various ways in order to improve the living conditions of the local community. This allowed to explore the processes through which urban nature was used as a strategic, mainstream measure to build livability in urban design and development. Analysis of presented examples shows that the biophilic cities go beyond mere provision of parks and preserving the nearby nature, but seek to actively entice and induce urbanites to enjoy nature and be part of it. Those kinds of solutions can help to provide in many ways the basis for healthier lives and lifestyles of local communities and should be considered more often in urban design.
Keywords: City; biophilic city; biophilic urbanism; local community.